Relationship between pathological gambling, alexithymia, and gambling type. (17th February 2017) - Bonnaire, Céline; Barrault, Servane; Aïte, Ania; Cassotti, Mathieu; Moutier, Sylvain; Varescon, Isabelle
Abstract : Background and Objectives: The aim of this study is to see if: (i) alexithymia is associated with PG and with the severity of gambling behavior; (ii) alexithymia is associated with strategic and non‐strategic gambling. Methods: Two hundred and twenty‐six gamblers were recruited in different gambling locations. First, pathological gamblers (PGs) ( n = 106) were compared to non‐pathological gamblers (NPGs) ( n = 120). Second, strategic gamblers ( n = 92) were compared to non‐strategic gamblers ( n = 96). Results: After controlling for being or not depressed, PGs have significantly higher alexithymia scores. Alexithymia is positively correlated to the intensity of gambling behavior and associated with PG: being alexithymic (OR = 4.21, SEB = .32, p < .001), "difficulty identifying feelings" (OR = 1.07, SEB = .03, p = .038), and "externally‐oriented thinking" (OR = 1.07, SEB = .03, p = .026) factors. Nevertheless, while alexithymia is associated with PG in strategic gamblers (being alexithymic (OR = 6.80, SEB = .50 p < .001) and "difficulty identifying feelings" (OR = 1.12, SEB = .05 p = .026) factor), this is not the case in non‐strategic gamblers. In the latter, only depression is associated with PG (OR = 3.43, SEB = .50 p = .013). Discussion and Conclusion: The results highlight the importance of taking into account the gambling type in the relationship between alexithymia, depression, and PG. Scientific Significance: In non‐strategic PGs, specific therapies targeting depression could be appropriate, while for strategic PGs, specific psychotherapeutic techniques like body‐centered psychotherapy could help them to differentiate feelings from bodily sensations. (Am J Addict 2017;26:152–160)